Wpływ wylewu słonych wód poprodukcyjnych na gleby leśne w okolicach Głogowa = Influence of salt mine-waters overflow on the forest soils in Głogów region - Greinert, Andrzej; Greinert, Henryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
European areas are in high level antropogenic transformed, even on covered with green areas. The nets are in this range one of ubiquitous elements. One from more dangerous pipelines are these sending not indifferent for natural environment liquids. To such pipelines belong these transported salted mine waters, steered to the lagunes. Damages of these pipelines causes the devastation of ground-water environment, flora and fauna.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); zasolenie; skażenie gleb; gleby leśne